Rediscovering the church fathers : who they were and how they shaped the church - Haykin, Michael A. G. (Crossway, 2011)
This book is an organized and convenient introduction to how to read the church fathers from AD 100 to 500. Michael Haykin surveys the lives and teachings of seven of the Fathers, looking at their role in such issues as baptism, martyrdom, and the relationship between church and state. --from publisher description